THE IMAGE OF THE HEAD OF AN EDUCATIONAL INSTITUTION: A RETROSPECTIVE CONTENT ANALYSIS OF THE CONCEPT - Lavrentieva Olena Oleksandrivna; Arbuzova Anastasia Andreevna (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article analyses the meaning and role of image in professional activity. The process of formation of the content of the «image» concept, its semantic connections and relations have been investigated in a historical retrospective from the Ancient World to until now. The features of the image concept interpretation in the management, pedagogy, psychology, and sociology spheres have been studied. It has been established that the image is the result of the perception of a person by various social groups; it is formed under the influence of a number of factors and mutually influential actions. The essence of the image is reflected by the concepts «fashion», «icon», «reputation», «prestige», «presentation (assessment)», «symbol». At the same time, in the social consciousness, the image is a value affecting the success of any activity. The relevance of shaping the image of the head of an educational institution has been clarified. It is noted that the head of an educational institution has a complex professional image, which serves as a management tool to achieve the strategic goals and objectives of that educational institution. Such an image affects the prestige of the institution, shapes a positive opinion and trust in the entire teaching staff, and ensures the quality of educational services. It was determined that the professional image of the head of an educational institution manifests itself in different ways for parents and applicants for education, for subordinates and colleagues, as well as for government agencies. It has been established that the image of the heads of an educational institution is a dynamic characteristic of their personality, contributes to the manifestation of internal attitudes, personal qualities, life positions, pedagogical and managerial skills and professionalism. It has been determined that the indicators of professional image include such features as: appearance, behaviour, peculiarities of communication and organization of pedagogical interaction in the professional sphere, the level of professional culture. It has been concluded that the shaping of the image is the process of implementing the program of self-development of the heads of an educational institution through hard work on themselves, in order to increase the level of their own professional and personal competencies.